Mechanical Properties of Bamboo Fibre Composite Incorporating Pulverized Fuel Ash - Ali, Maisarah; Saad , Siti Asmahani; Khairuddin, Noor Farah Elyani; Sidek, Ammar Hamzi; Md. Salim, Muhammad Faiz (Trans Tech Publications, Switzerland, 2015)
Abstract. This study reports the findings of an experimental investigation for bamboo fibre (BF) reinforced concrete board. In this research, all specimens were prepared at 0.4 water/binder ratio. There were two series of specimens namely A series and B series. The A group utilizes only ordinary portland cement (OPC) as binder. Meanwhile, series B specimens uses binary binders, which were combination of OPC and pulverized fuel ash (PFA) with PFA to OPC ratio of 0.2. The performance of flat board plates with different percentage of bamboo fiber ranging from 0% to 5% and 20% PFA incorporation of cement weight were tested for bending strength (flexural) and compressive strength in accordance to BS 5669: Part 1 for particleboards. Specimens are cured in water curing tank and tested at 3, 7 and 28 days for compression test. Meanwhile for flexural strength test, the specimens are tested at 28 days. It is found that flexural and compressive strength increases with addition of BF. The optimum compressive and flexural strength at 28 days are recorded with 3% incorporation of BF for both PFA and control samples. Therefore, utilizing natural fibre and waste material for partial substitution of cement content in producing internal wall paneling system could contributes to the economic appeal and promoting sustainable construction approach. Keywords: Fibre reinforced concrete board; natural fibre; bamboo fibre; pulverized fuel ash; compressive strength; flexural strength